Newton Homotopy Solution for Nonlinear Equations Using Maple14 - Abd. Rahman, Nor Hanim; Ibrahim, Arsmah; Jayes, Mohd Idris (Journal of Science and Technology, 2011)
Many numerical approaches have been suggested to solve nonlinear problems. Some of the methods utilize successive approximation procedure to ensure every step of computing will converge to the desired root and one of the most common problems is the improper initial values for the iterative methods. This study evaluates Palancz et.al’s. (2010) paper on solving nonlinear equations using linear homotopy method in Mathematica. In this paper, the Newton-homotopy method using start-system is implemented in Maple14, to solve several nonlinear problems. Comparisons of results obtained in terms of number of iterations and convergence rates show promising application of the Newton-homotopy method for nonlinear problems.